Motivations to Refuse or Participate in Self-Reported Delinquency Surveys: a Qualitative Study Among Belgian Juveniles in Custody - Grégoire, J. (European journal on criminal policy and research, 2023)
Several factors were investigated that relate to motivation about participation in self-reported delinquency (SRD) questionnaires among a specific and relevant population: youths in custody. Three research questions were identified: (1) explore the major reasons why a youth does or does not agree to participate in an SRD questionnaire; (2) examine the mode of questionnaire administration (Web or paper-pencil); and (3) examine the role of pre- and postpaid incentives. These questions were also investigated with regard to gender. The study included a sample of 30 youths from two Belgian custodial facilities (boys = 20, girls = 10; age 12-17 years) who initially agreed to or refused to participate in an SRD questionnaire. A focus group method was used to collect data across 3 steps, according to the research questions. Results identified 4 interrelated types of motives shared among boys and girls as they agreed to or refused to participate in the SRD questionnaire. The Web version of the questionnaire was slightly more preferred by all the samples, and the incentive was clearly perceived as useless or even harmful with respect to their motivation to participate. This article discusses implications for further research with juveniles in custody and the need to focus careful attention on how information about an SRD questionnaire is presented. An appendix with principal tips from this study is included with this article.